Partial Liver Kinase B1 (LKB1) Deficiency Promotes Diastolic Dysfunction, De Novo Systolic Dysfunction, Apoptosis, and Mitochondrial Dysfunction With Dietary Metabolic Challenge. Issue 1 (January 2016) - Miller, Edward J.; Calamaras, Timothy; Elezaby, Aly; Sverdlov, Aaron; Qin, Fuzhong; Luptak, Ivan; Wang, Ke; Sun, Xinxin; Vijay, Andrea; Croteau, Dominique; Bachschmid, Markus; Cohen, Richard A.; et al.
Abstract : Background: Myocardial hypertrophy and dysfunction are key features of metabolic heart disease due to dietary excess. Metabolic heart disease manifests primarily as diastolic dysfunction but may progress to systolic dysfunction, although the mechanism is poorly understood. Liver kinase B1 (LKB1) is a key activator of AMP‐activated protein kinase and possibly other signaling pathways that oppose myocardial hypertrophy and failure. We hypothesized that LKB1 is essential to the heart's ability to withstand the metabolic stress of dietary excess. Methods and Results: Mice heterozygous for cardiac LKB1 were fed a control diet or a high‐fat, high‐sucrose diet for 4 months. On the control diet, cardiac LKB1 hearts had normal structure and function. After 4 months of the high‐fat, high‐sucrose diet, there was left ventricular hypertrophy and diastolic dysfunction in wild‐type mice. In cardiac LKB1 (versus wild‐type) mice, high‐fat, high‐sucrose feeding caused more hypertrophy (619 versus 553 μm 2, P <0.05), the de novo appearance of systolic dysfunction (left ventricular ejection fraction; 41% versus 59%, P <0.01) with left ventricular dilation (3.6 versus 3.2 mm, P <0.05), and more severe diastolic dysfunction with progression to a restrictive filling pattern (E/A ratio; 5.5 versus 1.3, P =0.05). Myocardial dysfunction in hearts of cardiac LKB1 mice fed the high‐fat, high‐sucrose diet was associated with evidence of increased apoptosis and apoptotic signaling via caspase 3 and p53/PUMA (p53 upregulated modulator of apoptosis) and more severe mitochondrial dysfunction. Conclusions: Partial deficiency of cardiac LKB1 promotes the adverse effects of a high‐fat, high‐sucrose diet on the myocardium, leading to worsening of diastolic function and the de novo appearance of systolic dysfunction. LKB1 plays a key role in protecting the heart from the consequences of metabolic stress.